A multi-criterion based integrated methodology for the selection of expert system shell. (2017) - Singh, Yash Pal; Mishra, Rahul; Bedi, S.S.; Yadav, H.C.
Expert systems (ES) applications are being designed using expert system shell (ESS). Various ESSs are commonly available nowadays to design and develop the expert system in various fields. The options range from the choice of hardware platforms to the choice of computer languages and software interfaces. This study illustrates a method to select the most appropriate ESS where multiple criteria exist not only from functional requirements but also from technical and vendor-support perspectives. In the present study, an integrated approach is presented to help ES developers to select most suitable expert system shell among a set of existing alternatives for their current and future needs. For this purpose, a fuzzy TOPSIS integrated with entropy method is proposed to carry out ESS selection. The applicability of the proposed approach has been illustrated through a case study.